Working Capital and Financial Performance of Indonesian Manufacturing Companies: Before and During COVID-19 - Ruhadi, Ruhadi; Mai, Muhamad Umar; Sudradjat, Sudradjat (Politeknik Negeri Bandung, 2024)
This research intends to reveal two important thoughts related to changes in working capital policies before and during the COVID-19 pandemic in Indonesia. This is essential since most companies’ working capital policy is aggressive during the normal period but conservative during the difficult period (such as COVID-19), where the demand for products fall off due to a decrease in people's purchasing power. Further, this study attempts to investigate the impact of working capital on company financial performance for both time periods. This study used a sample of manufacturing companies listed on the Indonesian capital market from 2017 to 2021. The Wilcoxon signed-rank test was employed to assess changes in working capital policies while panel data regression was utilized as an analytical technique to test the impact of working capital policies on financial performance. This study reveals that, first, working capital policies measured by Cash Holding Level (CHL) expanded dramatically during COVID-19 but remained unchanged when being measured by Cash Interactive Effect (CIE) and Gross Working Capital Ratio (GWCR). Second, working capital policies prior to COVID-19 measured by CHL and CIE had a favorable and significant effect on company financial performance, measured by Return on Assets (ROA) and Return on Equity (ROE).